Re-Imagining Literacy and Language Education for Girls of Color. (December 2022) - Player, Grace D.; González Ybarra, Mónica
This introduction to a special issue on Girl of Color literacies explores the editors' purpose for creating the issue. Utilizing sociocultural definitions of literacy nuanced and bolstered by Women of Color theories of language and literacy, they establish an urgency to pursue research that is conducted with and for Girls of Color within the field of literacy. The editors articulate the goals of the special issue as well as provide proposed lines of inquiry the field must address to create research, pedagogies, and practices that are more loving toward Girls of Color and that honor their beautifully complex meaning-making practices.